A comprehensive renal vascular access clinic results in improved patient outcomes and reduced costs. Issue 3 (9th October 2016) - Thomas, Shannon D.; Ip, Eugenia C.; Katib, Nedal; Pugh, Debbie; Lennox, Andrew; Endre, Zoltan; Tan, Elaine; Ellery, Chris; Varcoe, Ramon L.
Abstract : Background: Management of vascular access for haemodialysis is a leading cause of morbidity and hospitalization in patients with end‐stage renal disease. We sought to evaluate the change in admission and procedural outcomes before and after the establishment of a vascular surgeon‐led comprehensive renal vascular access clinic (RVAC). Method: A retrospective clinical study was conducted after an RVAC was established in January 2013, with retrospective database created for the 24‐month period prior to and after. Results: The number of inpatient encounters for haemodialysis vascular access care fell over identical time periods before ( n = 193) and after ( n = 164) the RVAC was established. This reduction was associated with a significant decrease in length of stay (from 10.71 to 3.14 days; P = 0.0056) and thrombosed access procedures (from 32 to 16; P = 0.048). The proportion of emergency procedures fell (from 54.5 to 25.4%; P = 0.002) with a trend towards less arteriovenous fistula formations in the latter group (from 75 to 49; P = 0.099). There was also a trend towards fewer procedures in the latter group (from 195 to 151; P = 0.22). A case‐mix costing analysis showed an estimated reduction in mean admission cost from $25 883.15 to $9332.81 for those 2‐year periods, equating to a saving of $3.46 million associated with the introduction of the clinic. Conclusion: The establishment of an RVAC has led to a variety of objective performance outcome improvements, including a decrease in hospital admission, length of stay, revision and emergency surgeries, with associated cost saving. It reflects positive outcomes observed in other surgical specialties' clinics.